I Spoke to You with Silence : Essays from Queer Mormons of Marginalized Genders - Diamond, Lisa M. (Lisa Michelle); Smith, Jenn Lee; Pray, Kerry Spencer (Book collections on Project MUSE., 2022)
"I Spoke to You with Silence" is a collection of original essays and previously published writing that first appeared on blogs and social media outlets where self-identifying Mormons of marginalized genders share their thoughts anonymously without risking friendships, their marriages, their standing in the church, or their lives"--